Improving of the surface properties of NiTiCu shape memory alloy by oxidation - Kök, Mediha; Aydoğdu, Yıldırım; Dağdelen, Fethi; Ateş, Gonca (Dicle Üniversitesi, 2017)
NiTi and NiTi-based shape memory alloys are so often used in medical applications to show that thermoelastic martensitic transformation. The major disadvantage of these alloys although advantageous, is the element nickel in the alloy. Alloy used as implants in the body, nickel element may be harmful to the body by mingling blood. Many methods have been applied to eliminate this detrimental effect. One of these methods is to create a barrier oxide by oxidizing the surface of the alloy. Therefore, at 800, 900 and 1000 °C temperature, the oxidation process was applied on NiTiCu shape memory alloy which transforms at body temperature. After this oxidation process results, the oxidation rate constants for oxidation of indicator were increased. As a result of the SEM-EDX measurements, Nickel was found to be minimal on the surface of alloy. The Changes occurring in the transition temperature of the alloy subjected to the oxidation process were measured by Differential Scanning Calorimetry DSC . The ideal transformation was observed in alloys oxidized at 900 °C

NiTi ve NiTi bazlı şekil hatırlamalı alaşımlar termoelastik martenzitik dönüşüm gösterdiği için medikal uygulamalarda sıklıkla kullanılırlar. Bu alaşımlar avantajlı olmasına rağmen en önemli dezavantajı, alaşım içindeki Nikel elementidir. Vücut içinde implant olarak kullanılan alaşımda, Nikel elementi kana karışarak vücuda zaralı olabilir. Bu zararlı etkiyi yok etmek için birçok yöntem uygulanmıştır. Bu yöntemlerden biri alaşımının oksitleyerek yüzeyinde oksit bir bariyer oluşturmaktır. Bu nedenle Vücut sıcaklığında dönüşüm veren NiTiCu şekil hatırlamalı alaşıma 800, 900 ve 1000 °C de oksidasyon işlemi uygulanmıştır. Bu oksidasyon işlemi sonucu, oksitlenme hızını göstergesi olan oksidasyon sabiti değerinin sıcaklık artıkça artığı görülmüştür. Alaşımların SEM-EDX ölçümleri sonucunda yüzeyinde Nikel elementinin çok az olduğu görüldü. Oksidasyon işlemine tabi tutulan alaşımların dönüşüm sıcaklığında meydana gelen değişim Diferansiyel Taramalı Kalorimetre DSC ile ölçüldü. En ideal dönüşüm 900 °C de oksitlenen alaşımda görüldü
NiTiCu Şekil hatırlamalı Alaşımın Oksidasyon ile yüzey Özelliklerinin Geliştirilmesi